DESIGN INOVASI MEDIA FLASHCARD MAHASISWA PG PAUD UMSURABAYA UNTUK MENANAMKAN KONSEP MEMBILANG ANGKA 1 – 9 PADA ANAK USIA DINI - wahono wahono (Universitas Muhammadiyah Surabaya, 2016)
This study aims to inspire teachers (PAUD) and to gain an overview of the use flashcard media In Enhancing The Ability To Instill The Concept Of Counting Numbers 1‐9 In Early Childhood. Research was conducted on students The study program Teacher Education Early Childhood Education, University of Muhammadiyah Surabaya. Experience teaches counting the most widely experienced by children aged five and six years. 90% of the observation of early childhood teachers teach the concept of counting the numbers 1‐9 are correct. To strengthen the child's responses, teacher invites children to count the number of fingers together left hand and right hand. After the children were asked to try yourself counting the fingers of their left and right hands. From interviews with teachers and parents 85%, the They've been able to train children to count the objects that exist around children whether at home, on the road, as well as schools. From the observations gathered researchers found 75% of teachers and parents have not been used to teach counting while bernyannyi, children are introduced to the concept of numbers, for example through the songs that match the numbers that will be introduced, for example: the song I love mom. Keywords: flashcard media, count the numbers 1‐9